Informatics in Dental Education: A Horizon of Opportunity - Abbey, L. M. (Methods of Information in Medicine, 1989)
Computers have presented society with the largest array of opportunities since the printing press. More specifically in dental education they represent the path to freedom from the memory-based curriculum. Computers allow us to be constantly in touch with the entire scope of knowledge necessary for decision making in every aspect of the process of preparing young men and women to practice dentistry. No longer is it necessary to spend the energy or time previously used to memorize facts, test for retention of facts or be concerned with remembering facts when dealing with our patients. Modern information management systems can assume that task allowing dentists to concentrate on understanding, skill, judgement and wisdom while helping patients deal with their problems within a health care system that is simultaneously baffling in its complexity and overflowing with options. This paper presents a summary of the choices facing dental educators as computers continue to afford us the freedom to look differently at teaching, research and practice. The discussion will elaborate some of the ways dental educators must think differently about the educational process in order to utilize fully the power of computers in curriculum development and tracking, integration of basic and clinical teaching, problem solving, patient management, record keeping and research. Some alternative strategies will be discussed that may facilitate the transition from the memory-based to the computer-based curriculum and practice.
Keywords: Education; Attitudes Toward Computers; Health Education